A sequence variant in the phospholipase C epsilon C2 domain is associated with esophageal carcinoma and esophagitis. Issue 1 (6th February 2013) - Wang, Li‐Dong; Bi, Xiuli; Song, Xin; Pohl, Nicole M.; Cheng, Yulan; Zhou, Yixing; Shears, Stephen; Ansong, Emmanuel; Xing, Mengtao; Wang, Shaomeng; Xu, Xiao‐Chun; Huang, Peng; et al.
Abstract A single‐nucleotide polymorphism (rs2274223: A5780G:His1927Arg) in the phospholipase C epsilon gene (PLCϵ) was recently identified as a susceptibility locus for esophageal cancer in Chinese subjects. To determine the underlying mechanisms of PLCϵ and this SNP in esophageal carcinogenesis, we analyzed PLCϵ genotypes, expression, and their correlation in esophageal cancer cell lines, non‐transformed esophageal cells, 58 esophageal squamous cell carcinomas and 10, 614 non‐cancer subjects from China. We found that the G allele (AG or GG) was associated with increased PLCϵ mRNA and protein expression in esophageal cancer tissues and in esophageal cancer cell lines. G allele was also associated with higher enzyme activity, which might be associated with increased protein expression. Quantitative analysis of the C2 domain sequences revealed that A:G allelic imbalance was strongly linked to esophageal malignancy. Moreover, the analysis of 10, 614 non‐cancer subjects demonstrated that the G allele was strongly associated with moderate to severe esophagitis in the subjects from the high‐incidence areas of China (OR 6.03, 95% CI 1.59–22.9 in high‐incidence area vs. OR 0.74, 95% CI 0.33–1.64 in low‐incidence area; P = 0.008). In conclusion, the PLCϵ gene, particularly the 5780G allele, might play a pivotal role in esophageal carcinogenesis via upregulating PLCϵ mRNA, protein, and enzyme activity, and augmenting inflammatory process in esophageal epithelium. Thus, 5780G allele may constitute a promising biomarker for esophageal squamous cell carcinoma risk stratification, early detection, and progression prediction. © 2013 Wiley Periodicals, Inc.